Memberdayakan Umat Awam sebagai Fasilitator Katekese: Memperkuat Komunitas melalui Pelatihan - Tarihoran, Emmeria; Pius X, Intansakti (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
The active role of the laity in catechesis activities is vital in strengthening the ecclesial community. Unfortunately, however, awareness of the laity's contribution and involvement is still minimal in many Church circles. Efforts to empower the laity as catechesis facilitators have great potential to increase their participation in strengthening ecclesial communities. One of the work programs from Preaching the Good Shepherd Parish of Batu Diocese of Malang is this PKM, which aims to empower lay people as catechesis facilitators through intensive training programs. This study involved a participatory training method with a Role-playing model involving participants from the Parish of the Good Shepherd of Stone. The results of this training succeeded in increasing the laity's understanding of their roles and responsibilities in catechesis activities. The participants were able to hone their skills as facilitators and improve their catechetical knowledge and their communication skills. This activity aims to increase people's awareness of their duties and responsibilities in the Five Duties of the Church, especially in preaching. Through this activity, the Good Shepherd Parish of Batu Diocese of Malang can empower lay people as catechesis facilitators through effective training programs, improving their skills, knowledge, and understanding of the role.